2010
DOI: 10.1007/s11200-010-0027-5
|View full text |Cite
|
Sign up to set email alerts
|

3D inversion of DC data using artificial neural networks

Abstract: In this paper, we investigate the applicability of artificial neural networks in inverting three-dimensional DC resistivity imaging data. The model used to produce synthetic data for training the artificial neural network (ANN) system was a homogeneous medium of resistivity 100 :m with an embedded anomalous body of resistivity 1000 :m. The different sizes for anomalous body were selected and their location was changed to different positions within the homogeneous model mesh elements. The 3D data set was genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…According to Figure 11, the FBNN model with a value of 0.001 for η and 0.9 for α clearly enabled efficient training of the networks based on the statistical criteria. Moreover, by comparing with the previous study by Signh et al, 38 Neyamadpour et al, 39 Karmarkar et al, 40 and Winiczenko et al, 41 it was noted that this suggested value provides the better result. 18,20,42 Theoretically, more training datasets are not usually more accurate models due to the interaction between synthetic data and the model.…”
Section: Trainingmentioning
confidence: 53%
“…According to Figure 11, the FBNN model with a value of 0.001 for η and 0.9 for α clearly enabled efficient training of the networks based on the statistical criteria. Moreover, by comparing with the previous study by Signh et al, 38 Neyamadpour et al, 39 Karmarkar et al, 40 and Winiczenko et al, 41 it was noted that this suggested value provides the better result. 18,20,42 Theoretically, more training datasets are not usually more accurate models due to the interaction between synthetic data and the model.…”
Section: Trainingmentioning
confidence: 53%
“…Method Traditional machine learning converts real-world problems into mathematical models, trains historical data models, and finally converts the new data to real-world solutions. Among them, the artificial neural network is suitable for solving this kind of structure is complex changes of the underground geological inversion problem, not to need for data analysis and modeling, able to recognize and deal with the background and the law is not clear information [27][28][29], however, it is very hard to complex geological region has certain limitation, for example, hard training large networks and depth, In the inversion process, there are problems such as over-fitting, slow convergence rate and low accuracy [7,[30][31][32]. Based on this, domestic and foreign geophysicists have carried out in-depth research on this issue and put forward a series of improved methods, such as: Jiang et al proposed COSFLA optimization based on wavelet packet denoising and ANFIS network [33] and resistivity imaging inversion based on kernel principal component wavelet neural network based on ISFLA training [34], which achieved good results by using kernel principal component wavelet neural network.…”
Section: Based On Traditional Machine Learning Inversionmentioning
confidence: 99%
“…Jiang [27] use the 2D closed structure model to describe complex 2D soil structure, Onier et al [28] develop a 2D numerical model based on a numerical solver to analyse soil structure volumetric parameter. Also, more stereoscopic and accurate 3D soil stratified structures are more commonly used in geology [29][30][31], which could visualise the soil's electrical properties better.…”
Section: Introductionmentioning
confidence: 99%